Bread crust thickness estimation using L a b colour system - Mohd Jusoh, Yanti Maslina; Chin, Nyuk Ling; Yusof, Yus Aniza; Abd. Rahman, Russly (Universiti Putra Malaysia Press, 2008)
The crust formation of bread is imperative as it contributes to aroma, flavour and texture of the product. The extent of surface browning during formation of crust is suspected to correspond to the thickness of crust and gradually affects the quality of the bread produced. A method to distinguish the crust and crumb was developed using the L a b colour system. Commercial breads of different categories, sandwich, open and standing breads, were used as samples to set up the colour range for crust and crumb. In general, L is always higher in the crumb compared to crust. However, a and b values in crust are consistently higher than crumb which indicates the browning effect. The xE between crust and crumb in sandwich, open and standing breads were 30.98, 29.86 and 25.96, respectively. Bread crust is identified as the brown region with L value lower than 66, a value higher than 2.4 and b value higher than 22.3. Baking temperatures in the range of 175 to 200°C and baking times from 30 to 50 minutes were used to bake open loaves with different crust colours and thickness. Higher baking temperature and time are proven to produce bread with intense surface colour and thicker crust. The correlation between crust colour and its thickness shows good linear relationships indicating the possibility of predicting crust thickness using its surface colour.